Genome Sequence of Peacock Reveals the Peculiar Case of a Glittering Bird - Jaiswal, Shubham K.; Gupta, Ankit; Saxena, Rituja; Prasoodanan, Vishnu P. K.; Sharma, Ashok K.; Mittal, Parul; Roy, Ankita; Shafer, Aaron B. A.; Vijay, Nagarjun; Sharma, Vineet K. (Frontiers in Genetics, 2018)
The unique ornamental features and extreme sexual traits of Peacock have always intrigued scientists and naturalists for centuries. However, the genomic basis of these phenotypes are yet unknown. Here, we report the first genome sequence and comparative analysis of peacock with the high quality genomes of chicken, turkey, duck, flycatcher and zebra finch. Genes involved in early developmental pathways including TGF-β, BMP, and Wnt signaling, which have been shown to be involved in feather patterning, bone morphogenesis, and skeletal muscle development, revealed signs of adaptive evolution and provided useful clues on the phenotypes of peacock. Innate and adaptive immune genes involved in complement system and T-cell response also showed signs of adaptive evolution in peacock suggesting their possible role in building a robust immune system which is consistent with the predictions of the Hamilton–Zuk hypothesis. This study provides novel genomic and evolutionary insights into the molecular understanding toward the phenotypic evolution of Indian peacock.